Recent Progress in Self‐Supported Catalysts for CO2 Electrochemical Reduction. Issue 6 (19th February 2020) - Yang, Hengpan; Wang, Xiaodeng; Hu, Qi; Chai, Xiaoyan; Ren, Xiangzhong; Zhang, Qianling; Liu, Jianhong; He, Chuanxin
Abstract: Electrochemical reduction of CO2 may provide a promising method to mitigate the concentration of CO2 in the atmosphere, and simultaneously convert this greenhouse gas into value‐added fuels or chemicals. However, electrocatalysts for CO2 reduction are mostly powder based; therefore, polymer binders are always employed to make these catalysts useful as working electrodes. As a consequence, plenty of active sites are embedded inside without catalytic performance, causing a relatively low efficiency. On the contrary, self‐supported electrocatalysts do not involve the typical powdering and drop‐coating procedure with the aid of polymer binders or additives, avoiding the weak contact between active materials and current collector. Moreover, the superior self‐supported structure can also provide an accelerated electron transfer, guarantee ample electrolyte access to the active sites, offer large electrochemical surface areas, and increase CO2 adsorption capacity around the active sites, finally leading to the excellent efficiency and long‐term stability in CO2 reduction. In this manuscript, recent advances regarding CO2 reduction by self‐supported electrocatalysts are comprehensively reviewed, including the synthesis methods, chemical compositions, nanostructures, and catalytic efficiencies. Furthermore, the existing challenges and perspectives on the research and development of self‐supported electrocatalysts for CO2 reduction are discussed. Abstract : Recent advances regarding the CO2 reduction at self‐supported electrocatalysts are reviewed, including the synthesis methods, chemical compositions, nanostructures, and catalytic efficiencies. The existing challenges and perspectives on the research and development of self‐supported electrocatalysts for CO2 reduction are also discussed.